Correlation of Salusin Beta with hs-CRP and ADMA in Hypertensive Children and Adolescents - Kołakowska, Urszula; Kuroczycka-Saniutycz, Elżbieta; Olański, Witold; Wasilewska, Anna (Current Pharmaceutical Design, 2018)
Purpose: The emerging evidence has recently shown an evident dependence between recently identified salusin peptides and atherosclerosis, and their important roles as endogenous modulators of atherogenesis. It was reported that the development of atherosclerosis could also be affected by endogenous salusin- β overproduction in vascular lesions. Materials/Methods: This prospective cohort study was conducted in two groups of children: HT – 58 patients with essential hypertension (HT); R - 30 participants with white-coat HT (R). We analysed the relationship between serum salusin- α and salusin- β levels and ADMA, SDMA and hs- CRP in children and adolescents with essential hypertension. Results: Serum level of salusin- #145; in each sample was under the sensitivity of method. Serum level of salusin-β was statistically significantly higher in hypertension group when compared to the reference group (p<0.05) and correlated positively with serum hs-CRP [rho=0.47; p<0.01] and asymmetric dimethylarginine (ADMA) [rho=0.32; p<0.05]. There was no significant association between salusin-β and symmetric dimethylarginine (SDMA) [rho=0.27; p>0.05]. Conclusion: This preliminary study showed that the concentration of salusin-β is associated with circulating level of hs-CRP and ADMA in teenagers with hypertension. Further studies are needed to find out if salusin-β levels may indicate for endothelial dysfunction and form the basis for the development of new therapeutic agent.
Keywords: vascular lesions